Respuesta :
assuming cos2 x means cos^2 x, u can substitute y=cosx and the equation becomes: y^2 + 2y -2 =0
solving it gives the solution -1+-sqrt(3)
solving it gives the solution -1+-sqrt(3)
Answer:
Option D. 1
Step-by-step explanation:
Thinking process:
Let the quadratic equation be given by the formula:
[tex]cos^{2} x+ 2 cosx - 2 = 0[/tex]
then solving the equation using the factorization method:
using the trigonometry identity of cos 2x
then
[tex]Cos2x = 2cos^{2}x - 1[/tex]
Substituting 2Cos²x - 1 gives:
2[tex]cos^{2} x-1+cos^{2}x-2= 0[/tex]
rearranging gives:
[tex]3cos^{2}x = 3\\ cosx = \sqrt{1} \\ = 1[/tex]
hence cosx = 1